Individual socioeconomic status as a modifier of the association between high ambient temperature and hospital admissions: a time series study in Hong Kong, 2010–2019 - Yi Tong Guo; William Bernard Goggins; Emily Ying Yang Chan; Kin Fai Ho (Environmental Science and Pollution Research, 2022)
Few studies have examined individual socioeconomic status (SES) as a potential modifier of ambient temperature–health associations, especially for temperature-related hospitalizations. We fit penalized distributed lag non-linear models within generalized additive models to study the short-term associations (0–3 days) between temperature and hospital admissions stratified by common causes, age, and individual SES, as determined by whether patients received public assistance (PA) to cover their medical fee at the time of hospitalizations, during the hot season (May 15 to October 15) in Hong Kong for the years 2010–2019. We calculated the ratio of relative risk (RRR) and corresponding 95% confidence interval (CI) to statistically test the difference of the associations between PA groups. For 75 + patients, the PA group had significantly increased risks of hospitalizations at higher temperature for most causes, with relative risks (RR, 99th %ile vs. 25%ile) and 95% CIs of 1.138 (1.099, 1.179), 1.057 (1.008, 1.109), and 1.163 (1.094, 1.236) estimated for all non-cancer non-external, circulatory, and respiratory admissions, respectively. There were slight decreases of RRs with higher temperature for 75 + patients without PA. The strengths of temperature–hospitalization associations were strongly and significantly different between PA groups for all examined causes for 75 + patients, with the most considerable discrepancy found for ischemic heart disease (RRR = 1.266; 95% CI, 1.137, 1.410). Hospitalizations for patients aged 15–74 were less affected by heat, and the difference of the associations between groups was small. Individual SES is a significant modifier of high temperature–hospitalization associations in Hong Kong among the elderly. Public health interventions are needed to better protect this subpopulation from adverse health impacts of high temperature.

Air pollution associated with cognitive decline by the mediating effects of sleep cycle disruption and changes in brain structure in adults - Chen-Chen Lo; Wen-Te Liu; Yueh-Hsun Lu; Dean Wu; Chih-Da Wu; Ting-Chieh Chen; Yu-Ting Fang; Yu-Chun Lo; You-Yin Chen; Lo Kang; Cheng-Yu Tsai; Yueh-Lun Lee; et al. (Environmental Science and Pollution Research, 2022)

Health risks of adults in Hong Kong related to inhalation of particle-bound heavy metal(loid)s - Xiaocui Chen; Tony J. Ward; Chinmoy Sarkar; Kin-Fai Ho; Chris Webster (Air Quality, Atmosphere & Health, 2022)
Heterogeneity between ambient and personal exposure to heavy metals has been documented. However, few studies have investigated potential health risks posed by inhalational exposure to airborne heavy metal(loid)s at the individual level. A total of 404 personal fine particles (PM 2.5 ) samples were collected from 61 adult residents (aged 18–63 years) in Hong Kong during 2014–2015. Heavy metal(loid)s were analyzed using energy dispersive X-ray fluorescence. Among the analyzed heavy metal(loid)s, zinc (Zn) was the most abundant component in personal PM 2.5 , followed by lead (Pb), copper (Cu), and vanadium (V); cobalt (Co) and cadmium (Cd) were not detectable. Health risks of personal exposure to heavy metal(loid)s via inhalation were assessed for adults, including non-cancer risks that were characterized by hazard quotient (HQ) and hazard index (HI). The results indicated that non-cancer risks of heavy metal(loid)s were attributable to Cu, with a 95 th HQ value > 1. Arsenic (As) and hexavalent chromium [Cr (VI)] were also significant contributors to inhalation cancer risks (> 1 × 10 −6 ) for the adult participants. Finally, we employed a Monte Carlo simulation to evaluate the uncertainty associated with health risk assessment. The mean and median upper-bound lifetime cancer risk associated with inhalation exposure to carcinogenic heavy metal(loid)s exceeded the acceptable level (1 × 10 −6 ) for adults. Traffic emission (including non-tailpipe exhaust), shipping emission, and regional pollution were significant sources of heavy metals. These findings suggest that emission controls targeting local vehicles and vessels should be given priority in Hong Kong.

Organic carbon and acidic ions in PM2.5 contributed to particle bioreactivity in Chinese megacities during haze episodes - Kin-Fai Ho; Ya-Chun Lee; Xinyi Niu; Hongmei Xu; Renjian Zhang; Jun-Ji Cao; Cheng-Yu Tsai; Ta-Chih Hsiao; Hsiao-Chi Chuang (Environmental Science and Pollution Research, 2022)